Land-based climate mitigation strategies for achieving net zero emissions in India - Jaiswal, Deepak; Siddique, Khadeeja Mol; Jayalekshmi, T. R.; Sajitha, A. S.; Kushwaha, Amit; Surendran, Sruthi (Frontiers in Climate, 2025)
Despite advancements in electrification and the transition to solar-based electricity production, India will continue to depend on land-based carbon offsets to achieve its net-zero target. Land-based climate mitigation strategies in India can be implemented by utilizing underutilized marginal lands or increasing land availability through technological interventions to close agricultural yield gaps. Both below-ground (e.g., soil carbon) and above-ground (e.g., standing tree biomass) options offer viable pathways for such measures. Key strategies include cultivating perennial bioenergy feedstocks, afforestation, establishing fast-growing Miyawaki forests, restoring wetlands and mangroves, and applying biosolids to land. However, caution is essential to prevent unintended consequences, such as clearing natural forests or introducing microplastics into soils. The cost of carbon sequestration and the resilience or permanence of stored carbon will be critical factors in determining the preferred approach. Additionally, land-based strategies often overlap spatially, making GIS-based tools indispensable for identifying optimal solutions tailored to local conditions. Integrating these strategies into the national carbon budget can enhance transparency and contribute significantly to India’s net-zero emissions goal.